2022
DOI: 10.1038/s41598-022-11739-y
|View full text |Cite
|
Sign up to set email alerts
|

Alpha and beta phylogenetic diversities jointly reveal ant community assembly mechanisms along a tropical elevational gradient

Abstract: Despite the long-standing interest in the organization of ant communities across elevational gradients, few studies have incorporated the evolutionary information to understand the historical processes that underlay such patterns. Through the evaluation of phylogenetic α and β-diversity, we analyzed the structure of leaf-litter ant communities along the Cofre de Perote mountain in Mexico and evaluated whether deterministic- (i.e., habitat filtering, interspecific competition) or stochastic-driven processes (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 95 publications
1
4
0
Order By: Relevance
“…Contrary to what we observed in high-elevation sites, in low elevations, the species of genus Monomorium are as abundant as Cataglyphis species. This finding is in line with the study of Pérez-Toledo et al (2022) in Mexico, who reported that Monomorium is highly restricted to the warm conditions found in the lowlands. This could probably resemble the neotropical origin of this genus (Ward et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to what we observed in high-elevation sites, in low elevations, the species of genus Monomorium are as abundant as Cataglyphis species. This finding is in line with the study of Pérez-Toledo et al (2022) in Mexico, who reported that Monomorium is highly restricted to the warm conditions found in the lowlands. This could probably resemble the neotropical origin of this genus (Ward et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Second, the outcome of competition on phylogenetic structure is a consequence of invasion gradients, as competition from invasive plants produces phylogenetic clustering whereas competition between native plants produces phylogenetic overdispersion. The hypothesis that competitive groups will exclude noncompetitive groups leading to phylogenetic clustering has been weak (Gerhold et al., 2015 ; Lososová et al., 2016 ), whereas other studies find phylogenetic overdispersion due to competition (Pérez‐Toledo et al., 2022 ). The novelty of our findings is that phylogenetic structure is dependent upon the degree of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Ants (Order Hymenoptera, Family Formicidae) are one of the most important groups of insects, especially in the tropics (Folgarait, 1998; Wilson & Holldobler, 2005), and are a key component of the terrestrial food web, and their responses to abiotic, biotic, and functional changes suggests that they are a useful indicator group of environmental changes (Tiede et al., 2017). In general, various abiotic factors are thought to influence ant diversity, including the high environmental variation at different elevations (Pérez‐Toledo et al., 2022). With regard to hurricanes, however, the data examining the response of ant communities are lacking.…”
Section: Introductionmentioning
confidence: 99%